A case of primary malignant melanoma of the esophagogastric junction with abscopal effect after nivolumab administration - Takahisa Yamaguchi; Sachio Fushida; Jun Kinoshita; Hiroto Saito; Mari Shimada; Shiro Terai; Hideki Moriyama; Koichi Okamoto; Keishi Nakamura; Itasu Ninomiya; Noriyuki Inaki (Surgical Case Reports, 2021)
Abstract Background The abscopal effect is a rare phenomenon in which local irradiation causes tumor regression outside the irradiated area. There have been no reports of abscopal effect in patients with gastrointestinal melanoma with metastasis. Here, we report a case of primary malignant melanoma of the esophagogastric junction with abscopal effect after long-term treatment with nivolumab. Case presentation A 75-year-old woman was referred to our hospital with a gastroesophageal lesion. Upper gastrointestinal endoscopy revealed a raised lesion on the posterior wall of the greater curvature of the cardia and tenderness in the lower esophagus. Immunostaining of the tumor biopsy showed positive staining for Melan-A, human melanoma black-45 (HMB45), and S-100, indicating malignant melanoma of the esophagogastric junction. Contrast-enhanced computed tomography (CT) of the abdomen showed a mildly stained lesion protruding into the cardiac part of stomach and enlarged surrounding lymph nodes. The patient was diagnosed with malignant melanoma of the esophagogastric junction and proximal gastrectomy with lower esophagus resection was performed. Histological examination showed large, round tumor cells with nuclear atypia. Immunostaining was positive for Melan A, HMB45, S-100 protein, and SRY-box transcription factor 10, and the final diagnosis was malignant melanoma of the esophagogastric junction, with regional lymph node metastases. Three months after surgery, follow-up CT indicated left pleural metastasis; therefore, the patient was administered nivolumab, an immune checkpoint inhibitor (ICI). Following three courses of nivolumab, the patient exhibited grade 3 renal dysfunction (Common Terminology Criteria for Adverse Events version 5.0). After that, we have not administered nivolumab treatment. Five months after the development of renal dysfunction, a CT scan demonstrated an unstained nodule within the pancreatic, and the patient was diagnosed with pancreatic metastasis; intensity-modulated radiotherapy was performed. Six months later, CT revealed pancreatic nodule and pleural metastasis was shrunk; after an additional 2 months, pleural metastasis and effusion had disappeared. The patient is alive with no additional lesions. Conclusions We report a case of primary malignant melanoma of the esophagogastric junction with an abscopal effect following nivolumab treatment. The findings of this case report suggest that ICIs in combination with radiotherapy may be effective for treating metastatic or recurrent malignant melanoma of the gastrointestinal tract.